Tripod USPIONs with high aspect ratio show enhanced T2 relaxation and cytocompatibility - Wyss, Pradeep P.; Lamichhane, Surya; Rauber, Martin; Thomann, Ralf; Krämer, Karl W.; Shastri, V. Prasad (Nanomedicine, 2016)
Aim: We synthesized ultra-small iron oxide nanoparticles (USPIONs) with tripod morphology and studied the effect of the aspect ratio (AR) of the tripod arms on mass magnetization, T2 relaxation and cytocompatibility in human cell lines. Materials & methods: Tripods were prepared by controlling the temperature during the thermal decomposition of Fe(CO)5, and their magnetic properties were characterized by superconducting quantum interference device, and NMR. Citric acid stabilized USPIONs were used to assess cytocompatibility. Results: T2 relaxivity of tripods showed dependency on AR of the tripod arm. Liver enzyme levels in presence of tripods were comparable to spherical USPIONs, and surprisingly tripods induced lower levels of reactive oxygen species. Conclusion: Tripod USPIONs with high AR arms possess excellent magnetic properties and cytocompatibility for further exploration as MRI contrast agents.